Hermetia illucens larvae meal as partial fishmeal replacement in jade perch diet cultured in biofloc : growth performance, feed efficiency and consumer acceptance - Norhayati Zainorahim; Norhidayah Mohd Taufek; Poo Balan Ganesan; Yuan, Geok Annie Tan; Hanan Mohd Yusof (Penerbit Universiti Kebangsaan Malaysia, 2024)
A 12-week feeding trial on jade perch (Scortum barcoo) was conducted to evaluate the outcomes of partial substitution of fishmeal with black soldier fly larvae meal (BSFLM) in a biofloc system that requires minimal water exchange. The jade perch juveniles were subjected to three dietary treatments namely the 100% fishmeal (FM100), 50% BSFLM (BSF50), and a commercial diet (COM) with 20 individuals per treatment in triplicate tanks. Growth, feed efficiency, and body indices were measured throughout the feeding trial. There were no significant differences observed between the treatments in growth indicators such as the body weight gain (84.55 - 89.10 g), feed conversion ratio (1.77 - 1.87), specific growth rate (1.71 - 1.81 %/day), protein efficiency ratio (1.69 - 1.77), survival rate (90.00 - 98.48 %) and fillet yield (34.94 - 37.08 %). The condition factor is similar in all treatment groups ranging from 1.97 - 2.05. The crude protein and moisture content making up fish body composition are not statistically different among treatments, but higher crude lipids are obtained in the BSF50 (32.33 ± 5.27 g/kg) and COM (31.67 ± 2.76 g/kg). Higher hepatosomatic index (HSI) and visceral fat somatic index (VFSI) values were observed in BSF50 group at 3.13 ± 0.25 and 10.89 ± 1.68, respectively. Furthermore, sensory evaluation comparing the consumers’ evaluation and acceptance of the fish cultured with the different dietary treatment and culture system shows that the group fed BSF50 and cultured in biofloc system received similar overall appreciation with the FM100 and COM group. In conclusion, BSFLM inclusion in the jade perch diet, combined with the biofloc system, is feasible to be explored further.